Preparation of Ag(Shell)-Au(Core) nanoparticles by anti-galvanic reactions: are capping agents the ``real heroes'' of reduction? - Sahu, Puspanjali; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2015)
The formation of Ag(shell)-Au(core) nanoparticles by the reduction of Ag+ ions on preformed Au NPs, mediated by the capping agents like dodecylamine is described. We clearly established that while monodisperse Ag(shell)-Au(core) structures can be formed in presence of weak surface binding ligands such as amines, strong binding ligands such as thiols, lead to formation of separate monometallic Au and Ag particles. Apart from highlighting the influence of metal-ligand binding strength on the formation of core-shell nanoparticle architectures, our study also provides an easy means to produce Ag( shell)-Au( core) structures. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Ag(shell)-Au(core) nanoparticles; Anti-Galvanic reactions